Nature's fading chorus : (Island Press, 2000)
Naturalists in every age have been intrigued by frogs, toads, and salamanders. Nature's Fading Chorus presents an anthology of writings on amphibians drawn from the entire Western natural history tradition, beginning with Aristotle's Inquiry Concerning Animals written in the fourth century B.C.E., and continuing through recent scientific accounts of the relatively sudden - and alarming - global declines and deformities in amphibian species. The book is divided into five sections. The first three offer selections from the most influential contributors to the Western canon of natural history writing, and contain classic texts that illustrate central themes in the changing understanding of amphibians and of the natural world. The fourth section offers engaging essays by leading twentieth-century nature writers that portray a variety of amphibians in diverse terrains. Part five covers the various aspects of, and research on, the problem of amphibian declines and deformities.